(untitled) (Religious dialogue and cooperation, 2025)
This paper explores the phenomena arising from the complex interplay and multifaceted relationships between religion and the process of globalization. In comparative - descriptive manner we examines the mutual impact and relational dynamics between religion and globalization, analyzing the accompanying societal challenges: syncretism, secularization, homogenization, “world religion”, versus the genuine freedom of being, the spiritual aspiration toward Truth, and the authentic values that foster mutual human recognition of diversity, love, and cooperation. In doing so, the study offers insight into the position of religion, with the accent on Christian antropologie, within the process of globalization and how contemporary global trends influence the collective value system, shape traditional practices, form identity, and contribute to the emergence of current social anomalies and religious doctrines.